2015
DOI: 10.1177/1094428115571894
|View full text |Cite
|
Sign up to set email alerts
|

How Careless Responding and Acquiescence Response Bias Can Influence Construct Dimensionality

Abstract: We investigated the effects that careless responding and acquiescence response bias have on analyses conducted to assess construct dimensionality. Using job satisfaction/dissatisfaction as the focal construct, we measured and controlled for careless responding and acquiescence bias in data obtained from an online survey of employees (N ¼ 666) from different organizations and occupational groups. We found that the negative correlation between factors defined by job satisfaction and dissatisfaction items, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
117
0
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(147 citation statements)
references
References 35 publications
4
117
0
7
Order By: Relevance
“…These poor indices confirm the earlier finding that the common method bias is not detected in the data (Podsakoff & Organ, ; Mattila & Enz, ). Non‐response bias was tested through t‐test (Armstrong & Overton, ), where respondents with missing demographic values were considered non‐respondents (Kam & Meyer, ). All the constructs' data were not found to be significantly different, except the construct of environmental consequences.…”
Section: Data Analysis and Resultsmentioning
confidence: 99%
“…These poor indices confirm the earlier finding that the common method bias is not detected in the data (Podsakoff & Organ, ; Mattila & Enz, ). Non‐response bias was tested through t‐test (Armstrong & Overton, ), where respondents with missing demographic values were considered non‐respondents (Kam & Meyer, ). All the constructs' data were not found to be significantly different, except the construct of environmental consequences.…”
Section: Data Analysis and Resultsmentioning
confidence: 99%
“…The effect of IER on the linear correlation coefficient has been well documented [4,6,7], and conditions causing the magnitude of correlation to inflate have been characterized. Other studies have suggested that patterned careless responses in surveys with positively and negatively keyed items can lead to misleading conclusions about the dimensionality of constructs [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…These loyalty behaviors will benefit both market share and profitability for the service firm (Heskett et al, 1994(Heskett et al, , 1997 Job satisfaction is commonly defined as the extent to which employees enjoy their work (Suzuki et al, 2006;Lambrou, Kontodimopoulos and Niakas, 2010); it describes an attitude or feeling employees have towards their jobs (Price, 2001;Robbins, 2001 There are also different views on the structure of job satisfaction dimensions. Some scholars believe that job satisfaction is one dimensional (Nagy, 2002;Shah et al, 2011;Vukonjanski, Terek and Gligorović, 2014;Meyerding, 2015), and others think it is multi-dimensional (Oshagbemi, 1999;Miner, Dowson and Sterland, 2010;Johnson, 2012;Kam and Meyer, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%